China's new Navy the evolution of PLAN from the People's Revolution to a 21st century Cold War - Li, Xiaobing 1954- (Naval Institute Press, 2023)
"The book tells the story of successive generations of Chinese naval officers and sailors with modernization as the central theme and patterns of their operational behavior. The unique characteristics influence naval reforms amid political loyalty. The way the Chinese Navy both carried on longstanding traditions while made remarkable changes was crucial to building a "rich country with a strong navy.""--
Keywords: China / Zhongguo ren min jie fang jun / Hai jun / History; Sea-power / China; China / History, Naval / 1949-; Puissance maritime / Chine; Chine / Histoire navale / 1949-; HISTORY / Military / Naval; HISTORY / Modern / 20th Century / Cold War